Effects of compartment and severity of pelvic organ prolapse on voiding difficulty and overactive bladder: A case-control study with multiple outcomes - Apisith Saraluck; Orawee Chinthakanan; Komkrit Aimjirakul; Rujira Wattanayingcharoenchai; Jittima Manonai (PLoS ONE, 2026)
Background The current understanding of the relationship between different degrees of prolapse and the impact of prolapse in different compartments on voiding difficulty (VD) and overactive bladder (OAB) remains insufficient and requires further research. This study aimed to investigate the association between pelvic organ prolapse (POP) and the risk of VD and OAB. Methods A retrospective case-control study was conducted among women diagnosed with POP at urogynaecology clinic in a university hospital from January 2018 to December 2020. Patients were divided into two case events (VD and OAB) and a control group (POP without lower urinary tract symptoms [LUTS]). Associations between the site and severity of prolapse in the case and control groups were investigated to identify the factors involved in VD and OAB. Results The study included 151 cases of women with POP experiencing VD, 139 instances of OAB, and 151 women without LUTS in the control group. Most women with POP were postmenopausal, multiparous, and overweight. A multivariate logistic regression analysis revealed that the only factor associated with VD and OAB among women with POP was an advanced stage of anterior compartment prolapse (odds ratio [OR] 4.91, 95% confidence interval [CI] 2.36–10.25, p < 0.001, OR 2.28, 95% CI 1.09–4.78, p < 0.03, respectively). Conclusions An advanced stage of anterior compartment prolapse was the main factor that affected VD and OAB in women with POP.